SURFACE HARDENING HEAT TREATMENTS APPLIED TO CAST IRONS AND STEELS USED IN THE MANUFACTURE OF HEAT EXCHANGER SUBASSEMBLIES - Florin CIOFU; Alin NIOAŢĂ (Fiabilitate şi Durabilitate)
The paper presents methods to increase the service life of some subassemblies of the heat exchangers of thermal power plants. The phenomenon of cavitation, wear or corrosion are effects of the operating conditions of these subassemblies (pipes, valves, valves, elbows, connections, cooling systems). With a set of properly applied heat treatments, the service life can be increased by 70-80%. Simple or Duplex heat treatments were applied to samples taken from such obsolete subassemblies, after which wear tests were performed, the results being significant.